DEEPENING SINO-NEPAL RELATIONS: IMPLICATIONS FOR INDIA - Singh, Sudhir; Shekhar, Shashank (WILAYAH: The International Journal of East Asian Studies, 2023)
Nepal is extremely susceptible to outside influence because of its geostrategic position. Being a small, landlocked nation crammed between China and India, two of the most powerful nations in Asia. Nepal is always the target of regional aspirations and conflicts. In order to protect its independence and national security, Nepal’s foreign policy has focused on the difficult challenge of maintaining good relations with all parties. The paper discusses about the consequences of growing Nepalese affinity towards China on the long-time friend and neighbor state India from mid-20th century till today. Due to Nepal’s difficult democratic transition, frail institutional foundation, and unfavorable civil-military relations, China seems to have several possibilities to develop significant influence inside the country’s political and administrative system. Furthermore, the relationship between Kathmandu and New Delhi is severely impacted by NepalChina collaboration, particularly in the areas of security and defence. In conclusion, China’s increasing involvement in Nepal has significant security repercussions for New Delhi since it signals an entrance into the country’s sphere of influence. The paper attempts to categorically analyze these developments, firstly the paper discusses the geopolitical relevance of Nepal between India and China, further it elaborates on the historical links and the political and diplomatic engagements between these states. It also discusses the change in dynamics between the cold war period and post-cold war period. In conclusion, the paper aims to discuss the contemporary policy changes and challenges for New Delhi. The paper concludes with an understanding that balancing is the most viable option that is present for the states involved.